Technology-Assisted Collaborative Writing: EFL Students’ Perceptions and Preferred AI Features for Literature Reviews - Dwiansari Ramadhani; Roro Millatu Al Ghaniy; Ning Difani Wulan (Universitas Pendidikan Mandalika, 2026)
Despite technology-assisted and AI-based tools have been commonly used in supporting academic writing in English as a Foreign Language (EFL) context, particularly in collaborative learning environments, research on how EFL students perceive the use of integrated AI and collaborative platforms specifically in research-based writing, as well as which features they find most beneficial remain limited. This study fills in the gap by exploring EFL students’ perceptions of technology-assisted tools in collaborative literature review writing and to identify the AI-supported features they perceive as most helpful. Employing a descriptive qualitative design, data were collected through open-ended questionnaires administered to 33 students and follow-up semi-structured interviews with six selected participants. The findings revealed that students perceived technology-assisted tools positively as they enhanced efficiency, productivity, accessibility, collaboration, and their overall perspective on academic writing. Preferred AI features included information retrieval and research support, idea generation and content development, language improvement, and collaboration support. Despite these positive perceptions, students also expressed concerns regarding ethical issues, authorship, and over-reliance on AI. The findings suggest that technology-assisted collaborative tools help students improve their research writing by supporting the writing process, developing critical thinking skills, and teaching responsible technology use. To ensure the effective and ethical use of these tools, educational policies should include clear guidelines.